Effect of repeated intraperitoneal injections of different concentrations of oxycodone on immune function in mice - Chen, Sumeng; Liu, Jingjing; Huang, Shaoqiang (Frontiers in Pharmacology, 2024)
Background The effect of oxycodone as an opioid receptor agonist on immune function is still controversial. In this study, we investigated the possible effects of oxycodone on immune function in mice and its possible mechanisms of action. Methods By repeated intraperitoneal injections of 25 mg/kg morphine and 5 mg/kg, 20 mg/kg, and 60 mg/kg oxycodone, we assessed possible changes in the number of splenic lymphocytes and inflammatory cytokines in the serum of mice. CD4+ T cells and CD8+ T cells were sorted from the spleen to observe whether the expression levels of opioid receptors and downstream signals were altered. Results Repeated administration of oxycodone at a dose above 20 mg/kg resulted in significant weight loss. Repeated administration of oxycodone exhibits significant dose-dependent reduction in CD4+ T cells, with little effect on CD8+ T cells and little effect on inflammatory cytokine levels. Low- and intermediate-dose oxycodone increased the mRNA expression level of MOR, KOR, and DOR to varying degrees. Moreover, oxycodone increases the mRNA expression levels of the TLR4 signaling pathway to varying degrees. Conclusion Repeated intraperitoneal injection of oxycodone induces immunosuppression in mice.